Drug use on both sides of the US-Mexico border - Guilherme Borges; Sarah E Zemore; Ricardo Orozco; Cheryl J Cherpitel; Priscilla Martínez; Lynn Wallisch (Instituto Nacional de Salud Pública, 2018)
Objective. To compare drug use for cities along the US-Mexico border. Materials and methods. Data are from the US-Mexico Study on Alcohol and Related Conditions (UMSARC, 2011-2013), a survey of 4 796 randomly selected Mexican and of Mexican origin individuals on both sides of the border. Results. Higher rates of any past-year drug use and symptoms of drug use disorders were found only in the border city of Laredo, when compared to the non-border city of San Antonio. Nuevo Laredo and Reynosa/Matamoros showed higher rates of drug use than the non-border city of Monterrey. Much higher rates (OR's in the range of 4-11) were found in the US cities when compared to their across the- border Mexican counterparts. Conclusions. Drug use is high on the border for the selected Mexican cities. Misuse of prescription drugs is nevertheless a concern in the south Texas border cities in our study.